2010
DOI: 10.1097/acm.0b013e3181cd2ed3
|View full text |Cite
|
Sign up to set email alerts
|

Linking Practice-Based Research Networks and Clinical and Translational Science Awards: New Opportunities for Community Engagement by Academic Health Centers

Abstract: Purpose Practice Based Research Networks (PBRNs) are a part of many National Institutes of Health (NIH) funded Clinical and Translational Science Award (CTSA) sites. PBRNs, groups of primary care practices committed to collaborating on practice-relevant research, are unfamiliar to many CTSA leaders. Conversely, the CTSAs, as new research structures designed to transform clinical research, are unfamiliar to many PBRN Directors. This study examined the extent to which these programs have congruent goals and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 24 publications
0
59
0
Order By: Relevance
“…This is consistent with observations from other investigators that PBRNs are increasingly engaging in formal relationships with other research organizations, including CTSAs. 9 The current analysis suggests, however, that formal relationships with CTSAs are still in preliminary stages and have not yet resulted in more research projects per year, nor has CTSA affiliation resulted in a significant difference in self-reported research capacity, as explored in this article.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with observations from other investigators that PBRNs are increasingly engaging in formal relationships with other research organizations, including CTSAs. 9 The current analysis suggests, however, that formal relationships with CTSAs are still in preliminary stages and have not yet resulted in more research projects per year, nor has CTSA affiliation resulted in a significant difference in self-reported research capacity, as explored in this article.…”
Section: Discussionmentioning
confidence: 96%
“…Eliciting collaboration between clinical and public health stakeholders to identify joint research needs and generate practice-based evidence could help bridge the current divide between them. In their article, "Linking Practice-Based Research Networks and Clinical and Translational Science Awards: New Opportunities for Community Engagement by Academic Health Centers," Fagnan and colleagues (22) describe survey results from CTSA and PBRN leaders that suggest the potential for such collaborations.…”
Section: What Are Public Health Pbrns?mentioning
confidence: 99%
“…Clinical and Translational Science centers are interested in PBRNs not only for their role in conduct of research in real-world settings but also for their potential to speed the translation of clinical research findings into everyday practice. 17 The Agency for Healthcare Research and Quality's recent call for applications for statewide demonstration-type projects aimed at catalyzing the transition of practices to patient-centered medical homes suggests the potential for PBRNs in supporting health systems change at the practice level. 18 Participation in PBRN studies has been shown to benefit practices beyond the goals of the specific study being conducted.…”
Section: Organization Of Clinical Practicementioning
confidence: 99%